Influence of queen mothers on the honeybee hive varroa mite population in the year 1998 - Janez POKLUKAR (Acta Agriculturae Slovenica, 1999)
Varroa mite population was studied in 317 hives located in 40 apiaries in July 1998. Queens originated from 46 mother queens were reared at 16 different rearing locations in Slovenia. Diagnostic treatment represented 10 ml of 85 % formic acid applied on the bottom board. Fallen mites were counted 48 hours after treatment. We found a highly significant effect of the apiary on the varroa infestation by using the analysis of variance. Queen rearing locations and mother queens nested within queen rearing locations did not affect a level of varroa infestation significantly. LSMEAN estimate extracted two mother queens with extremely small varroa population (Kropivšek b/97 and Vozelj 1/97). There was no evidence of a colony having a significantly higher level of varroa mite infestation than tested population of bees. Highly infested colonies yielded approximately 2 kg less honey than less infested bee colonies.